Metagenomic identification of a new sarbecovirus from horseshoe bats in Europe - Jack M. Crook; Ivana Murphy; Daniel Carter; Steven T. Pullan; Miles W. Carroll; Richard Vipond; Andrew A. Cunningham; Diana Bell (2021)
Abstract The source of the COVID-19 pandemic is unknown, but the natural host of the progenitor sarbecovirus is thought to be Asian horseshoe (rhinolophid) bats. We identified and sequenced a novel sarbecovirus (RhGB01) from a British horseshoe bat, at the western extreme of the rhinolophid range. Our results extend both the geographic and species ranges of sarbecoviruses and suggest their presence throughout the horseshoe bat distribution. Within the spike protein receptor binding domain, but excluding the receptor binding motif, RhGB01 has a 77% (SARS-CoV-2) and 81% (SARS-CoV) amino acid homology. While apparently lacking hACE2 binding ability, and hence unlikely to be zoonotic without mutation, RhGB01 presents opportunity for SARS-CoV-2 and other sarbecovirus homologous recombination. Our findings highlight that the natural distribution of sarbecoviruses and opportunities for recombination through intermediate host co-infection are underestimated. Preventing transmission of SARS-CoV-2 to bats is critical with the current global mass vaccination campaign against this virus.